Effect Of Risk Management Practices On The Financial Performance Of Commercial Banks In Iraqi - Mohd Sam, Mohd Fazli; Zuhair Khudhair, Ayad (Opción, 2019)
During the last years, banks have been facing heavy mergers and acquisitions, in particular, universal and commercial banks all over the world. Such activities hamper the degree to which the Financial System is included and decrease the public’s trust. The research aims to demonstrate the need to pay more attention to risk management for banks. In this study, the main issue was to examine how risk management activities in Iraqi commercial banks help boost these banks ‘ performance. The study revealed that the key variable to evaluate the performance of the commercial banks is risk management. The study further stated, when counterparties fail to meet their commitments, risk management substantially impacts the financial performance of commercial banks.